2015
DOI: 10.1155/2015/612029
|View full text |Cite
|
Sign up to set email alerts
|

Interface Shear Actions and Mechanical Properties of Nanostructured Dissimilar Al Alloy Laminated Metal Composites

Abstract: The laminated metal composites (LMCs) of dissimilar metals (aluminium alloys: AA1100/AA7075) were fabricated using the accumulative roll bonding technique in conjunction with cold rolling. The LMCs of ultrafine grained AA1100 and nanostructured precipitates of AA7075 achieved metallurgical bonding. The microstructure of the bonding interfaces and constituent metals was investigated using scanning electron microscopy and transmission electron microscopy for the LMCs with different layers. The deformation incomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(103 reference statements)
1
4
0
Order By: Relevance
“…The AA7050 layers are the strengthening phase in this multilayered composite and the work hardening curves showed that the hardening behavior was controlled by this macrostructural constituent. Necking and fragmentation of this layer reduces the ductility because stress concentrates at these points, and is in accordance with other results in the literature (Govindaraj et al, 2013;Chen et al, 2014;Chen and Chen, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The AA7050 layers are the strengthening phase in this multilayered composite and the work hardening curves showed that the hardening behavior was controlled by this macrostructural constituent. Necking and fragmentation of this layer reduces the ductility because stress concentrates at these points, and is in accordance with other results in the literature (Govindaraj et al, 2013;Chen et al, 2014;Chen and Chen, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…More specifically, (Chen et al, 2014) studied the same class of alloys used in this work, and observed that yield strength, tensile strength, and elongation decreased with the increase of variation of interface shape when the number of layers was kept constant. When the scale was reduced, in other words, decreasing the layer thickness below 6 µm (Chen and Chen, 2015), the different layers interacted with the dislocation glide process and an increase in yield stress and elongation was observed. This is similar to the case of 8 cycles in both processes in present work.…”
Section: Discussionmentioning
confidence: 99%
“…indicates that severe work-hardening was attained during cold rolling [14,22,36,37]. According to the literature [38][39][40][41], lamination processing induces extra strainhardening at the contacting surfaces of two adjacent laminae (interface-affected-zone).…”
Section: Monotonic Notch Tensile Testingmentioning
confidence: 99%
“…In turn, back stress strengthening, and back stress work-hardening established at the strain-hardened interfaces confine dislocation motion within the layers, and powerful reinforcing mechanism are activated in the whole laminate. Outstanding laminate toughening due to pre-delamination effect has also been reported under such circumstances [38][39][40], whereby cracks nucleate in every formed interface-affectedzone, leading to high energy consumption during crack propagation caused by in-plane shear stresses. This toughening effect can be confirmed by comparing stress-strain curves of unnotched specimens in Figs.…”
Section: Monotonic Notch Tensile Testingmentioning
confidence: 99%
“…e layer metal laminated materials were made of two or more single-layer metals by suitable composite technology [7][8][9]. It combined the advantages of single-component metal, which not only made the application value of single metal fully play but also can reduce the amount of precious metal, improve the deficiency of single metal, and better adapt to the industrialization and market-oriented development [10][11][12].…”
Section: Introductionmentioning
confidence: 99%